Embelin and Levodopa Combination Therapy Mitigates Parkinson's Disease Complications in Mice - Koppal, Anand; Sivanesan, Senthilkumar; Ramachandra, Vagdevi Hangarakatte; Sukumar, Ethirajan; Vijayaraghavan, Rajagopalan (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: The present work evaluated the neuroprotective potential of embelin either alone and in combination with Levodopa in rotenone induced PD (Parkinson’s disease) model mice. Methods: Swiss albino male adult mice were randomly divided into 7 groups. Group-1 (Control) received 2mL/kg olive oil by oral route (p.o.), Groups from 2 to 7 were induced with 2.5mg/kg rotenone by intraperitoneal route (i.p.), levodopa was administered to Group-3. Group-4 and Group-5 were given 20mg/kg and 40mg/kg embelin p.o. Group 6 and 7 were given embelin p.o. at dose of 20 mg and 40 mg/kg respectively and also 7.5 mg/kg Levodopa p.o. At the end of the experiment (22nd day), blood was withdrawn by retro-orbital puncture to estimate various biochemical parameters and organs such as liver and brain, were dissected for histopathological and histochemical studies. Results: Drug treatment with a combination of embelin (40 mg/kg) and levodopa (7.5 mg/kg) to PD mice showed better neuroprotective activity than the remaining drug treatment groups based on the results from biochemical, histopathology and α-synuclein protein immunohistochemistry. Conclusion: The current in-vivo research showed that mice treated with embelin at a dose of 40 mg/kg b.w. along with reduced levodopa (7.5 mg/kg) standard therapy was effective to ameliorate rotenone induced PD complications.
Keywords: Parkinson’s disease; Swiss albino mice; Rotenone; Embelin; Levodopa